Harmonization of corporative tax - general guidelines in the EU and harmonization in Germany, Austria and Italy - Hodžić, Sabina (Naše gospodarstvo, 2012)
The European Union faces problems stemming from the diversity of corporate tax rates as member states apply their individual national rates for corporate taxes. The main objectives of this paper are to outline the situation in the harmonization of corporate tax in the European Union, especially as regulated in Germany, Austria and Italy, and to establish the objectives for the introduction of a common consolidated corporate tax base in the European Union. This paper examines corporate tax and the issues related to the harmonization of corporate tax. This paper also focuses on characteristics of corporate tax in Germany, Austria and Italy. The objectives for introducing a common consolidated corporate tax base and harmonizing corporate tax play a significant role in all European Union member states.
Keywords: European Union; Evropska unija; davki; tax; davčni sistemi; davek od dobička; harmonizacija